PEDAGOGICAL VIEWS ON MORAL AND CHRISTIAN EDUCATION PERSONALITIES IN LITERARY MONUMENTS XVI - FIRST HALF OF XVIII CENTURY (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the principles of Christian moral education reflected in literary works of the XVI - the first half of the XVIII centuries both in Ukraine & Russia.
Keywords: interciltural education; foreign languages education; intercultural aspect of foreign languages teaching